Residual PRE & POST Corn Herbicides with BAS 821 for Weed Control in Corn - Damian Franzenburg; Iththiphonh Macvilay (Hello World!, 2024)
The purpose of this study was to compare various herbicides used in one-pass Preemergence (PRE), one-pass postemergence (EPOST) and two-pass (PRE+POST) programs for crop injury and weed control in corn.